TINJAUAN YURIDIS WASIAT WAJIBAH TERHADAP ANAK ANGKAT DI DALAM KOMPILASI HUKUM ISLAM - Ferlinda Ayu Oktafila (Jurnal Ilmiah Dinamika Hukum, 2017)
In Indonesia, there has been no unification or no entity which regulates adoption. Fostering or adoption is still causing problems for communities and governments. Not only in terms of the appointment, but also the problem of the division of property of the adoptive parents. Based on this, the authors raised the title "Judicial Review was borrowed against Children Raise In The Compilation of Islamic Law (Case Study sues Inheritance Case Number: 029 / Pdt.G / 2014 / PTA.Smg)".The formulation of the problem of legal writing this study is (1) How was borrowed Against Judicial Review Adopted In KHI (Compilation of Islamic Law)? (2) How does the provision of the foster child is based on was borrowed from the estate of her adoptive parents in the case of contested inheritance case Number : 029 / Pdt.G/ 2014 / PTA.Smg? This study uses normative juridical approach to the specification of descriptive analytical research, the research aims to describe the legal review inheritance rights of adopted children according to Islamic Law Compilation (Case Study sues Inheritance Case Number: 029 / Pdt.G / 2014 / PTA.Smg). Besides, in this study, the authors used secondary data consisting of secondary law and primary legal materials. How to collect data through library research. Library method is done by examining the primary legal materials, and secondary on granting was borrowed against adopted children. Research results obtained are based on a review of juridical was borrowed against the adopted child in Compilation of Islamic Law, a foster child who did not inherit from his adoptive parents can get the name of administration, where the provision of children's lift can be done through was borrowed, as stated in Article 209 KHI , Giving the foster child is based on was borrowed from the estate of her adoptive parents in the case of contested inheritance case Number: 029 / Pdt.G / 2014 / PTA.Smg namely, the adopted child can receive inheritance from her adoptive parents or heir through "was borrowed" a maximum the amount of 1/3 (one third) part of the overall property adoptive parents as article 209 Compilation of Islamic Law in Indonesia, with the proviso is not an heir and has not received agrant.